Analysis of Firm Value Using Financial Ratios and Board of Directors Characteristics Through the Tobin's Q Method - Bella Aldama Hardi Rahayu; Euis Mufahamah; Harold Kevin Alfredo (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of inclusive culture and promotion flexibility on the performance of ASN through employee engagement as a mediating variable to improve public services of ASN in the Pringsewu Regional Government. The research method used is a quantitative approach with Structural Equation Modeling (SEM) analysis through SmartPLS. The data used are primary data from ASN respondents via questionnaire and secondary data on ASN regulations in a certain research period. The results of the study show that inclusive culture and promotion flexibility partially have a significant effect on the performance of ASN. Employee engagement has been proven to play a significant role as a mediating variable in the influence of both on the performance of civil servants and public services. This finding implies that strengthening inclusive culture and promotion flexibility through employee engagement has an important role in optimizing the performance of civil servants, so the leadership of the Pringsewu Regional Government needs to implement inclusivity training policies and merit-based promotion reforms to improve public services.